The Effect of Different Access Cavity Designs in Combination with WaveOne Gold and TruNatomy Instrumentation on Remaining Dentin Thickness and Volume - Vorster, Martin; van der Vyver, Peet J.; Markou, George (My University, 2023)
The purpose of this study was to evaluate and compare 2 different access cavity designs in combination with 2 popular single-file preparation systems to see which combination preserves dentin, more specifically pericervical dentin, best. The minimum remaining dentin thickness and dentin volumes were evaluated pre- and postinstrumentation.
Keywords: Endodontic access cavity; TruNatomy; WaveOne Gold; micro–computed tomography; pericervical dentin